CULTURE AND FOOD OF UTTAR PRADESH: A HISTORICAL STUDY - Gaur, Abhishek; Gupta, Aarti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Food habits are generally dependent on two major factors, namely availability and accessibility. Food habits never change suddenly. Noticing the changes in food habits of any place is a long-term process. Hence, the main objective of this study is to assess the impact of partition of the country and its struggle to achieve food sufficiency as well as its effect on hunger and the diversity of food habits in different districts of Uttar Pradesh along with some of their unique food habits. The methodology of this study is historical and qualitative. This research relies on secondary sources, such as government annual reports and gazetteers. The study reveals that the transfer of power in the medieval period greatly affected food. Muslim influence came to India during the Sultanate period and soon they adopted some of the specialties of the local cuisine and invented their own distinctive fusion dishes. Mughlai cuisine was also born in a similar way but it was very rich and since the reign of Mughal rulers was very long they got enough time to pay attention to cultural and culinary development. The arrival of Europeans brought various global ingredients and cooking methods, dishes and cutlery to India. They used it not for the betterment of the society but for their commercial gains and flaunted western superiority. But the colonizers saved themselves by getting influenced by the Indian culture, food and ingredients which led to the birth of a new community i.e. Anglo Indian community and some distinctive dishes like curries, stews, desi chicken etc. The country faced severe food crisis.